2013
DOI: 10.2174/1570162x11311010006
|View full text |Cite
|
Sign up to set email alerts
|

Low-Abundance Resistant Mutations in HIV-1 Subtype C Antiretroviral Therapy-Naive Individuals as Revealed by Pyrosequencing

Abstract: Given the recent scale-up of antiretroviral therapy (ART) in sub-Saharan Africa, we sought to determine how often and at what levels do drug-resistant mutant variants exist in ART-naïve HIV subtype C infected individuals. Samples from 10 ART-naïve Zambian individuals were subjected to ultra-deep pyrosequencing (UDPS) to characterize the frequency of low-abundance drug resistance mutations in the pol gene. Low-abundance clinically relevant variants were detected for nucleoside reverse transcriptase inhibitors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…We could not establish whether or not this mutation contributes to resistance to entry inhibitors. The prevalence of I323V mutations has been reported to range from 3.8% to 7.1% [48,49]. In our study, we found a prevalence of 8.0% in plasma and 7.7% in the CSF sequences.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We could not establish whether or not this mutation contributes to resistance to entry inhibitors. The prevalence of I323V mutations has been reported to range from 3.8% to 7.1% [48,49]. In our study, we found a prevalence of 8.0% in plasma and 7.7% in the CSF sequences.…”
Section: Discussionsupporting
confidence: 56%
“…We found 61.5% and 60.0% of sequences from plasma and CSF, respectively, harbouring A316T mutation. A high prevalence of this mutation substantiates the finding that A316T is a natural polymorphism found in HIV-1C [48]. We could not establish whether or not this mutation contributes to resistance to entry inhibitors.…”
Section: Discussionsupporting
confidence: 54%